Why the QWERTY-phenomenon is not just "in the minds of theorists" and why it could nonetheless be no problem in reality - Jens Weghake; Fabian Grabicki (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2016)
Researchers disagree about the relevance of the so called QWERTY-phenomenon which simply means to get stuck in a bad equilibrium. There exists two contrary parties. One side says that the major influence for market success comes from greater quality. In consequence an inferior market player should not persist and the possibility of the QWERTY-phenomenon is denied by this party. The opposite side emphasize the importance of network effects which can lead to lock-ins in inferior situations. This papers investigates this debate. We demonstrate that the missing consideration of the status quo bias in previous studies leads to a rejection of the QWERTY-phenomenon. We give several examples of different industries with inferior market share leaders. However, we suggest that this phenomenon is just a temporary harm and the lock-in could be overcome by a specific form of Schumpeterian creative destruction. Therefore we claim that even if lock-ins exist it is no problem as long as innovative market participants have the opportunity to develop and introduce new business models.
Keywords: D43; L13; O33; O38; 330; platform selection; two-sided markets; status quo bias; QWERTY-phenomenon; creative destruction